RESPON KAPAS (Gossypium hirsutum L.) TERHADAP PUPUK KALIUM PADA VERTISOL DI BANGKALA JENEPONTO - PETER TANDISAU; MUHAMMAD BASIR NAPPU; M. AZIS BILANG (Jurnal Penelitian Tanaman Industri, 1998)
Response of cotton (Gossypium hirsutum I.) to potassium fertilizer at vertisol Bangkala JenepontoThe study on the response of cotton o potassium on upland was carried out in vertisol Bangkala Jeneponto, South Sulawesi. The experiment was held on January 1994 to July 1994. The teatments consisted of seven rates of Potassium fertilizers viz : 0, 15, 30, 45, 60, 75 and 90 kg K20/ha or equal to 0, 25, 50, 75, 100, 125 and 150 kg KCI/ha. The teatments were arranged in a randomized block design, with four replications. The esearch results indicated that cotton responded to potassium applications. Potassium ertilizer could improve cotton esponded o potassium applications. Potassium ertilizer could improve coton growth and yield component, and seed cotton production. The response curve was still linear. The moe KCI applied, the better the cotton growth and yield component, and the seed cotton yield. The application of Potassium ertilizer 125 kg KCI or 75 kg KjO/ha on coton planted on vertisol Bangkala Jenepono produced seed coton yield I 911 kg/ha.